2022
DOI: 10.3390/en15093113
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture 5.0: A New Strategic Management Mode for a Cut Cost and an Energy Efficient Agriculture Sector

Abstract: The farmers’ welfare and its interlinkages to energy efficiency and farm sustainability has attracted global scientific interest within the last few decades. This study examines the contribution of Agriculture 5.0 to the prosperity of the farmers in the post-pandemic era and the gradual transition to an energy-smart farm. To obtain an insight into the attributes of Agriculture 5.0 and the emerging technologies in the field, Bibliometrix analysis with the use of an R package was conducted based on 2000 data con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…Additionally, the forestry component of ICLF systems, crucial for emissions reductions in these production systems, covered less than 2 Mha in Brazil in 2015 (EMBRAPA, 2017). Simultaneously, we have taken a conservative approach toward Agriculture 5.0 technologies (Ragazou et al., 2022) by assuming an exogenous yield increase (Supporting Information), which captures some of these expected technological advances. While beyond the scope of our study, emerging biotechnologies such as lab‐cultured meat, algae‐based feed and renewable hydrogen‐based protein production have the potential to significantly reduce the environmental footprint of food systems.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the forestry component of ICLF systems, crucial for emissions reductions in these production systems, covered less than 2 Mha in Brazil in 2015 (EMBRAPA, 2017). Simultaneously, we have taken a conservative approach toward Agriculture 5.0 technologies (Ragazou et al., 2022) by assuming an exogenous yield increase (Supporting Information), which captures some of these expected technological advances. While beyond the scope of our study, emerging biotechnologies such as lab‐cultured meat, algae‐based feed and renewable hydrogen‐based protein production have the potential to significantly reduce the environmental footprint of food systems.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that cross-compliance is an efficacious tool for promoting environmental and agricultural sustainability [81][82][83][84]. However, some scholars have argued that cross-compliance alone may not be sufficient to meet the environmental goals of the CAP [85], and a thorough combination with other policy instruments, such as agri-environmental measures and payments for ecosystem services, could be indispensable [81,85].…”
Section: From Policy Reform To Environmental Stewardship: Examining T...mentioning
confidence: 99%
“…The agriculture sector, as the oldest production activity with a rural origin, has been of special importance in the process of growth and development of different countries over different periods of time (Ragazou et al, 2022). Examining the development process of different countries indicates that the development of the agricultural sector as one of the most important economic sectors for the realization of the sustainable development of the country is a vital matter (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%